Framing the Pandemic and the Rise of the Digital Surveillance State (Czech Journal of International Relations, 2020)
The pandemic caused by the SARS-COV-2 virus has provided a pretext for many countries of the world to extend executive powers, and their digital surveillance capacities in particular. Aiming to identify how different regimes frame digital surveillance, this paper employs qualitative content analysis to compare the government framing of digital surveillance in India, Israel and Singapore. Although due to their different working dynamics, one would expect democracies and autocracies to frame digital surveillance in different ways, our findings reveal an overlap between liberal and illiberal rhetoric across the cases and point to unexplored illiberal peculiarities within the category of ‘democratic backsliders.’ We conclude by cautiously speculating how heightened extents of digital surveillance and trackingmay become the new normal across regime types, and how governments might exploit and recycle these same frames to justify digital surveillance after the COVID-19 crisis is over.
Keywords: digital; surveillance; privacy; human rights; framing; regime types; democratic backsliding